KNOWLEDGE OF SHARIA BANKING ON THE INTEREST IN SAVING OF THE COMMUNITY IN NANGKA BINJAI UTARA VILLAGE VIEWED FROM SOCIAL DEMOGRAPHY ASPECT - Marlina Deliana; Nadia Amelia Poluan; Nasrullah Hidayat (Quantitative Economics Journal, 2022)
This study aims to determine the knowledge of Islamic banking in the North Binjai community, especially in Kampung Nangka Village. As many as 60% of the population in the North Nangka Binjai sub-district have a livelihood as traders. The sample in this study was 30 people and used a non-probability sampling technique, namely the snow ball in determining the sample. Questionnaire Data analysis techniques use a single table. The results showed that banking knowledge of interest in saving in terms of demographic aspects. Based on the questionnaire that had been distributed, the responses given by 50 respondents indicated that they agreed with knowledge of Islamic banking products. As many as 28 people of the female sex with an age range of 21-25 years with recent education, mostly high school students, having an average income of 500,000-1,000,000 said they agreed that knowledge about Islamic bank products was easy to understand. This was mostly chosen by mothers who graduated from high school with an income of 500,000-1,000,000. then, most of the respondents agreed that knowledge about Islamic bank products was easy to understand so that they became interested in opening savings accounts in Islamic banks in the future._______________________________________________________Keywords: Islamic Banking, Interest in Saving, Social Demographics